The structure of the U.S. economy in 1980 and 1985 : projections of gross national product, its income and demand composition, input-output relations, and output, productivity, and employment. - United States (Washington : U.S. Dept. of Labor, Bureau of Labor Statistics : for sale by the Supt. of Docs., U.S. Govt. Print. Off., 1975)
This book reveals some of the U.S structure of 1980 and 1985. It also contains the projections of employment by industry based on the labor force and potential gross national product (GNP)
Includes bibliographical references.
asm; 23/01/19
Loans
Keywords: Economic forecasting; United States